Regional order: to preserve the dignity without the «revolution of dignity» - Yaskevich, Yadviga S. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
Meaningful models of preservation of integrity, self-sufficiency and dignity of the country without social revolutions and shakes are considered in so-called «middle countries». It is argued that the policy of non-alignment or neutrality is the best way to preserve the dignity of the country without social revolutions and shaking in the national interest.